Population Pharmacokinetic Modeling of VL-2397, a Novel Systemic Antifungal Agent: Analysis of a Single- and Multiple-Ascending-Dose Study in Healthy Subjects - Kovanda, Laura L.; Sullivan, Sean M.; Smith, Larry R.; Desai, Amit V.; Bonate, Pete L.; Hope, William W. (Antimicrobial agents and chemotherapy, 2019)
VL-2397, a novel, systemic antifungal agent, has potent in vitro and in vivo fungicidal activity against Aspergillus species. Plasma concentrations from a phase 1 study were used to construct a population pharmacokinetic (PPK) model for VL-2397. VL-2397, a novel, systemic antifungal agent, has potent in vitro and in vivo fungicidal activity against Aspergillus species. Plasma concentrations from a phase 1 study were used to construct a population pharmacokinetic (PPK) model for VL-2397. Healthy subjects aged 18 to 55 years received single doses of VL-2397, ranging from 3 to 1,200 mg, multiple daily doses of 300, 600, or 1,200 mg for 7 days, or 300 mg three times/day for 7 days followed by 600 mg daily for 21 days. Plasma samples were collected throughout the dosing intervals. Sixty-six subjects provided 1,908 concentrations. Drug concentrations over time were increased less than dose proportionally for doses above 30 mg. Dose-normalized concentrations plotted over time did not overlap. A 3-compartment nonlinear saturable binding model fit the data well. Clearance increased with dose, and mean values ranged from 0.4 liters/h at 3 mg to 8.5 liters/h at 1,200 mg. Mean volume in the central compartment ranged from 4.8 to 6.9 liters across doses. In the first 24 h, once-daily dosing results in a rapid decrease in concentrations by hour 16 to approximately 1 mg/liter, regardless of dose, with slow clearance over time. Administration of 300 mg every 8 h achieved concentrations above 1 mg/liter over an entire 24-h period. There was a significant relationship between body surface area and clearance. The data suggest that VL-2397 has nonlinear saturable binding kinetics. Protein binding is the likely primary source of the nonlinearity. The PPK model can now be used to optimize dosing by bridging the kinetics to efficacious pharmacodynamic targets.